2007
DOI: 10.1111/j.0021-9029.2007.00155.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acute Alcohol Intoxication on Person Memory: The Stereotypical Drunk1

Abstract: Research has suggested that acute alcohol intoxication disrupts cognitive functioning by reducing the availability of executive resources for person perception. The present study tested the prediction that this effect would increase stereotype application during impression formation by reducing the encoding of nonstereotypical information. Participants were instructed to complete an impression-formation task following consumption of low, medium, or high doses of alcohol. This task involved the encoding of both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…According to law enforcement experience, on average, real-world witnesses are more intoxicated than 0.080 g/210 L when witnessing a crime (e.g., Evans et al, 2009), possibly resulting in more impaired cognitive processes than reflected in this study. Although differences in cognitive performance have been found in previous studies between 0.080 g/210 L BrAC levels and sober/placebo groups (e.g., Cunningham et al, 2007), none examined memory for autobiographical events. However, BrAC levels of more than 0.08 will be difficult to include under controlled experimental conditions without significantly increasing participants' risk level.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…According to law enforcement experience, on average, real-world witnesses are more intoxicated than 0.080 g/210 L when witnessing a crime (e.g., Evans et al, 2009), possibly resulting in more impaired cognitive processes than reflected in this study. Although differences in cognitive performance have been found in previous studies between 0.080 g/210 L BrAC levels and sober/placebo groups (e.g., Cunningham et al, 2007), none examined memory for autobiographical events. However, BrAC levels of more than 0.08 will be difficult to include under controlled experimental conditions without significantly increasing participants' risk level.…”
Section: Discussionmentioning
confidence: 84%
“…Second, how much and how accurately people remember depends on recall format—for both sober and intoxicated individuals (e.g., Curran & Hildebrandt, 1999). However, few studies on alcohol and memory have included recall instructions similar to witness recall conditions (e.g., Cunningham, Milne, & Crawford, 2007; Garfinkel et al, 2006); instead they have used recognition-test formats, despite the fact that witnesses are likely to provide a description of the observed event in a free format. Arguably, differences in response bias and metamnemonic functioning may be differentially reflected in free recall formats and recognition tests.…”
mentioning
confidence: 99%
“…The effect of alcohol on witness memory might therefore depend on the type of activity/level of distraction during an event to be remembered, and the resulting attentional or encoding deficits. Further supporting alcohol myopia, Cunningham, Milne, and Crawford (2007) found that increased intoxication was associated with impaired free recall for neutral but not stereotypical items. They argued that, after stereotype induction, the intoxicated only encoded the salient stereotype congruent information, at the expense of neutral stimuli, because of the fewer available cognitive resources.…”
Section: Alcohol and Memory Performancementioning
confidence: 87%
“…People are more likely to rely on pre-existing knowledge structures, such as stereotypes, when faced with high processing demands such as dual-task completion or high cognitive load (see Sherman, Lee, Bessenoff, & Frost, 1998) or when cognitive resources are scarce due to environmental factors such as time constraints or alcohol consumption, (Cunningham, Milne, & Crawford, 2007;Kruglanski & Freund, 1983;Rothbart, Fulero, Jensen, Howard, & Birrel, 1978).…”
Section: Youngmentioning
confidence: 99%